Failure analysis of Al2O3–C–SiO2 slide gate plates during continuous casting based on numerical simulation - Bing Tang; Zhiyan Lu; Fengxian Li; Fajin Zhu; Jianhong Yi; Yichun Liu; Jürgen Eckert (Journal of Materials Research and Technology, 2023)
The thermo-mechanical and failure behavior of the burning-free Al2O3 –C–SiO2 slide gate plate materials during the steel casting process are investigated. Firstly, the instantaneous coefficient of thermal expansion and the Young's modulus of the slide gate plate materials with different component contents at high temperature are measured. Secondly, a material constitutive model and a concrete damage plasticity mode are established based on the experiments, and adopted to simulate the failure behavior of the burning-free Al2O3–C–SiO2 slide gate plate during casting based on Finite Element Method (FEM) analysis. Results show that temperature gradient in the slide gate plate near the casting hole increased significantly and had a significant influence on cracking. The area near the casting hole of the slide gate plate is under tensile stress conditions, and then changes towards compressive stress conditions. Under those severe thermal stress conditions, crack formation is evaluated and an optimized composite structure of the slide gate plate combining advantages of reducing the risk of cracking and extending the service life is proposed. Moreover, the thermal shock test further verified that the microcrack extension was significantly alleviated due to the SiC distributed in whisker form and formed an interlocking structure in material. This work provides a reliable theoretical and experimental basis for the design and optimization of high performance Al2O3–C–SiO2 slide gate plates.